Technological advances in probiotic stability in yogurt: a review (Research, Society and Development, 2021)
Yogurt is one of the fermented dairy products widely produced and recognized around the world, in addition it is considered excellent vehicle for probiotics, which are live microorganisms that provide beneficial effects to the individual when consumed in adequate amounts. Thus, the aim of this literature review was to address the factors that affect the viability of probiotics in yogurt during the processing steps (heat treatment, homogenization, and fermentation), storage (acidification rate, pH, carbohydrate fraction, organic acids, oxygen, temperature, time, water activity and moisture content), consumption (gastric juice and bile salts) and shelflife (addition of other ingredients and packaging). However, to preserve the probiotics stability in yogurt and improve the quality and shelf life of products, several new technologies such as microencapsulation, ohmic heating, ultrasound, the addition of prebiotics, and advances in the use of packaging in production with an emphasis on improving the viability, are used and allow secure the minimum recommended level of at probiotics least 109  CFU per gram of product when consumed to have a beneficial effect on health and, moreover, they guarantee the growth and probiotics protection without influencing the flavor, from the production stage until the delivery of these in the gastrointestinal tract. Therefore, it is recognized from this research the need to optimize new technologies in the food environment, seeking to improve consumer products with increasingly favorable purposes for health.